2021
DOI: 10.1080/02687038.2020.1852001
|View full text |Cite
|
Sign up to set email alerts
|

An Umbrella Review of Aphasia Intervention descriPtion In Research: the AsPIRE project

Abstract: Background: Recent reviews conclude that aphasia intervention is effective. However, replication and implementation require detailed reporting of intervention is and a specification of participant profiles. To date, reviews concentrate more on efficacy than on intervention reporting quality. Aims: The aim of this project is to review the descriptions of aphasia interventions and participants appearing in recent systematic reviews of aphasia intervention effectiveness. The relationship between the quality of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…The completeness of the intervention description in this review was comparable to an umbrella review of intervention descriptions in aphasia [118]. The umbrella review, 50% of studies scored 8 out of a possible 12 items, and in this review 9/14 (64%) studies scored 8 or more out of the possible 12 items.…”
Section: Discussionmentioning
confidence: 53%
“…The completeness of the intervention description in this review was comparable to an umbrella review of intervention descriptions in aphasia [118]. The umbrella review, 50% of studies scored 8 out of a possible 12 items, and in this review 9/14 (64%) studies scored 8 or more out of the possible 12 items.…”
Section: Discussionmentioning
confidence: 53%
“…In complex behavioural interventions, the multiple planned elements of the intervention are interconnected, such that isolating and describing the therapeutic elements of a complex behavioural intervention is challenging. While study design and treatment tasks are frequently reported in aphasia trials, the theoretical underpinnings and potential active ingredients within the intervention are reported much less often [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of 93 studies, less than 30% reported actual or planned fidelity in aphasia treatment studies with information on where the treatment was provided, individual treatment tailoring, and modification rarely reported [9]. Reviews of treatment fidelity processes confirm limited treatment fidelity reporting in aphasia treatment studies [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Fidelity of aphasia treatment is currently an important focus of research both in terms of implementation and reporting (e.g. Brogan et al, 2019;Conlon, Braun, Babbitt & Cherney, 2020;Dipper, Franklin, de Aguiar, Baumgaertner, Brady, Best et al, 2021). It is acknowledged that, historically, fidelity has been poorly addressed in aphasia research (e.g.…”
Section: Fidelity Of Sentence Production Treatmentsmentioning
confidence: 99%